Effect of Design of Uniform Packing Characteristic to Improve Cooling Tower Performance - Muhaimin, Ahmad; Bin Sies, Mohamad Farid (Research Progress in Mechanical and Manufacturing Engineering, 2025)
An experimental study of the effect of uniform packing design oncooling tower performance is presented in this thesis, with a focus oncontrasting a newly developed Uniform Packing New Design (UPND)with a Previous Packing Design (UPPD) and a Non-Uniform Packing(NUP) configuration. Thermal performance is assessed under a range ofoperating conditions, including inlet water temperatures of 35°C, 43°C,and 50°C, and water flow rates ranging from 25 to 200 kg/h, using alaboratory-scale cooling tower apparatus (Model HE 152). The primaryfactors that were looked at were the tower characteristic (KaV/L) andthe cooling efficiency. The results show that the UPND does much betterthan the UPPD in all tested conditions. The tower characteristic valueswere 0.35, 0.39, and 0.37, which is an improvement of 52%, 86%, and76%, respectively. UPND also showed better cooling efficiency acrossthe tested temperature range, with values of 64.59%, 57.05%, and54.89%, which was up to 54.3% better than UPPD. The betterperformance is due to better contact between water and air, a moreeven flow distribution, and the removal of thermal dead zones in thepacking structure. NUP worked best at certain liquid-to-gas (L/G) ratios,but UPND worked well and consistently over a wider range of L/G ratios(0.20 to 1.70), showing that it can handle changing load conditions. Thestudy finds that the uniform packing design not only improves heatrejection and thermal stability, but it also fits with sustainable energygoals by lowering entropy generation and fan energy use. These resultsshow that UPND is a practical and high-performance option forindustrial cooling systems. They also help make cooling towertechnologies that are more efficient, reliable, and good for theenvironment.